Pemetaan Total Perilaku Opportunistic Terhadap Future Market Performance Studi Kasus Dampak Kebijakan Dividen Pada Kualitas Laba - Muljanto Siladjaja (Journal of Research in Business, Economics, and Education, 2020)
This empirical research has tested how the investor had detected the opportunistic behaviour in publishing the accounting information by indicating the earnings quality. The investor take a strong pressure on the management to obtain the high obedience on the accounting standard, because of predicting the future performance precisely. This research found one phenomenon about dividend policy in Indonesia company because it had been reduced the level of internal conflict. The dividend policy had been capable of attaining the higher shareholders involvement, indirectly obtained the higher accruals quality. This research tested on how the accruals quality and tax management influences in the investor’s perception in the future, that measured by future market value. The observation data had used the samples on the listed company in industry manufacturing sector for period 2015 until 2017, that categorized as LQ 45. The samples have amounted 250 observation in testing on the multiple regression model, which used the discretionary accruals quality and future market value. This empirical research has pointed out that the accruals quality has a positive influence on future market value, the higher of accruals quality value indicates the higher future market value. This moderation have pointed out the accruals quality has the positive impact on the future market value and played a critical role as informal communication in disseminating “the good sign” about the future prospect. The dividend policy has not moderated the tax management on the future market value. By developing out the Decision Tree Model with Teorema Bayes, the interactive feedback between the investor and the management by analyzing the accounting information, this is purely a implication of game theory. The high yielded dividend is obstacle for management, because of the cash flow operation’s liquidity performance, the update regulation should force the management on implementing the policy regularly and permanently.